MacCallum Plaque Causes Acute Myocardial Infarction in a Young Man. Issue 12 (24th March 2015) - Lu, Tse-Min; Yeh, Yi-Chen; Lu, Yen-Wen; Sung, Shih-Hsien; Wu, Fei-Yi; Hsu, Chiao-Po
Abstract : Supplemental Digital Content is available in the text.